Assessment of acoustic and thermal properties of airtight wooden windows used in Baltic and Scandinavian countries - Kęstutis Miškinis; Raimondas Bliūdžius; Vidmantas Dikavičius; Arūnas Burlingis (Journal of Environmental Engineering and Landscape Management, 2019)
Windows are the one of the most important elements of a building envelope. Windows with appropriate acoustic and thermal properties can guarantee comfort and protection of indoor environment. The sound and thermal insulation of windows are influenced by various factors and one of them is air tightness. The aim of this study was to assess if airtight typical wooden windows used in Baltic and Scandinavian countries always have both good acoustic and thermal properties. For this purpose, sound reduction index (characterizes acoustic properties), thermal transmittance (characterizes thermal insulation properties) and air permeability (characterizes air tightness) of windows were determined in the laboratory. The results showed that airtight windows have various acoustic and thermal properties. This means that there is a negligible relationship between air permeability and acoustic properties, also between air permeability and thermal properties of windows.